Credit Default Swaps - Theoretical pricing and practical calculation of a CDS for Peruvian corporate bonds using the Bloomberg platform - Yapo Quispe, Karen Milagros (2018)
This paper focuses on the valuation of a CDS for Peruvian corporate bonds, using the tools and real data provided by the Bloomberg platform, to illustrate the CDS pricing model of Hull and White (2000), considering the effects of probability of non-compliance, the amount of loss, the recovery rate and the time "t" of non-compliance.